The Influence of Reciprocal Teaching Towards the Critical Thinking Skill Improvement of Blind Students - Novi Indriastuti; Sugini Sugini; Mohammad Anwar (The Center for Disability Studies and Services Brawijaya University, 2020)
This study aims to determine the influence of reciprocal teaching application in improving the critical thinking skill of visually impaired student in SLB-A YKAB Surakarta on the academic of year 2019/2020. This study is classified as pre-experimental research with the form of one group pretest-posttest design. The Subjects in this study were seven students from 5th-9th grades in SLB-A YKAB Surakarta. The seven students became the research subjects after being selected using purposive sampling technique. Some subject criteria set in this study include: visually impaired student who have reached formal operational stage according to Piaget’s theory, were able to read, write, listen, and speak fluently, and have problems in developing critical thinking skills. Data collection in this study was done through observation and oral test. The instrument used in this study was validated by measurement expert, psychologist, and linguist and was tested to visually impaired students in SMP MIS Surakarta. The results of expert validation and instrument trials indicate that this instrument was valid with a validity coefficient of 0.92-1 and reliable with a reliability coefficient of 0.975. Then the instrument was used to measure the critical thinking skill of research subject before and after being given treatment through the application of reciprocal teaching. The pretest and posttest data were analyzed using non-parametric statistic with Wilcoxon Sign Rank Test type at the significance level of 0.05. According to the data analysis using SPSS 25, the Asymp. Sig (2-tailed) value was obtained of 0.017. That value was smaller than 0.05, so that H0 was rejected and Ha was accepted. Thus, the application of reciprocal teaching has a significant effect towards the critical thinking skill of visually impaired student in SLB-A YKAB Surakarta on the academic of year 2019/2020.